Nonlinear Approach For Determining Design Criteria For Yield Pillar Performance - W. Smith (International Conference on Ground Control in Mining, 1995)
The U.S. Bureau of Mines (USBM) is using laboratory and computer-based techniques to investigate the post- failure behavior of yielding pillars and pillar reinforcement techniques to control entry deformation. Poorly dimensioned yield pillars, can cause adverse ground conditions. Laboratory studies to evaluate various reinforcement techniques for controlling yield pillar deformation were conducted. A cracking and crushing model is used to evaluate potential tensile and compressive failure planes within pillars of various widths to assess the degree of yielding and stress redistribution. The use of an elasto-plastic model to evaluate the effect of various reinforcement on yield pillars is also discussed. These procedures effectively account for the residual pillar strength, important in yield pillar design.